(untitled) (Literary Voice, 2024)
Despite an array of new statutes designed to safeguard women and punish abusers, Intimate Partner Violence (IPV) continues to snuff out many lives leading to infringement of fundamental human rights and serious physical and mental health consequences. Like other societal phenomena, gender-based violence particularly IPV alongside its resistance, is prominently depicted in contemporary Indian cinema. By evaluating three films in light of a social responsibility paradigm which relies on realistic representation as its basic dimension, this research investigates how accurately IPV is portrayed across contemporary Indian cinema. The behavioural elements of the widely recognized The Duluth Model and Power and Control Wheel will be applied to determine realistic representation of IPV in each particular movie. This study focuses on films like Jasmeet K. Reen’s Darlings, Charukesh Sekar’s Ammu and Vipin Das’s ‘Jaya Jaya Jaya Jaya Hey’ which premiered in year 2022 in Hindi, Telugu and Malyalam cinema respectively. The results demonstrate significant variations in the measure of social responsibility indicating that contemporary Indian cinema may play a significant role in realistic projection of IPV